2015
DOI: 10.1007/s10334-015-0483-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological noise in human cerebellar fMRI

Abstract: likely to improve the temporal signal-to-noise ratio (SNR) for cerebellar fMRI at 7T, even at high spatial resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…In addition, the locations close to the lung may benefit from our approach, because such a location is more sensitive to respiratory-induced B 0 fluctuations. 22 Second, the qualitative and quantitative relationship between the state of respiration and the fluctuations of B 0 / B 1 1 field is unknown, because we monitored only the success of breath holding using the respiratory belt. Third, only the GRE sequence was examined for clinical images in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the locations close to the lung may benefit from our approach, because such a location is more sensitive to respiratory-induced B 0 fluctuations. 22 Second, the qualitative and quantitative relationship between the state of respiration and the fluctuations of B 0 / B 1 1 field is unknown, because we monitored only the success of breath holding using the respiratory belt. Third, only the GRE sequence was examined for clinical images in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] These B 0 fluctuations are mainly induced by susceptibility changes caused by lung and chest motion during breathing, as well as by other physiological noises, such as cardiac function, and blood and cerebrospinal fluid (CSF) pulsation. 22 B 0 mapping, which uses the difference between two phase images, is affected by the respiration-induced phase variations. 23 In addition, these B 0 changes have an impact on B 1 1 mapping of the BS method, because this technique uses the phase images with two different off-resonance pulses.…”
mentioning
confidence: 99%
“…Effects due to temporal autocorrelation of the acquired time series data, which can invalidate assumptions of normality, were minimised by prewhitening (Woolrich, Ripley, Brady, & Smith, 2001). It has been demonstrated that the cerebellum, like the brainstem, suffers from issues relating to increased physiological noise, for example, due to pulsatile flow of CSF through the fourth ventricle (Brooks et al, 2008;Brooks, Faull, Pattinson, & Jenkinson, 2013;van der Zwaag, Jorge, Butticaz, & Gruetter, 2015). Hence, a physiological noise model, which attempts to model signal fluctuation in the fMRI time series produced by cardiac and respiratory processes (Brooks et al, 2008) was incorporated into the GLM.…”
Section: Model Estimation Was Performed Using Feat (Fmrib's Expertmentioning
confidence: 99%
“…Multishot sequences are particularly prone to physiological noise, because different segments will be affected differently by respiration, cardiac rate, and more generally, motion. Physiological noise correction on 3D data led to small improvements in BOLD detection compared with standard 2D EPI for nonaccelerated 3D EPI at 7 T (19,29) and accelerated 3D EPI at 3T (20). Because segmented 3D EPI approaches are more susceptible to physiological fluctuations than 2D sequences, the advantage of using 3D accelerated sequences may not directly translate into a higher image SNR.…”
Section: Introductionmentioning
confidence: 99%